How to influence total costs of sourcing? A case study of SCOPQ with Six Sigma (International Journal of Applied Research in Management and Economics, 2021)
Total cost of sourcing is receiving significant attention from firms in general and purchasing managers in particular. Academic research on lean and six sigma programs has evolved rapidly in the last decade. This study focuses on uncovering most effective sourcing initiatives, which aim to decrease total costs addressing quality issues and Supplier Costs of Poor Quality (SCOPQ). This research aims to update the literature on supply chain management by analysing and verifying the proposed Six Sigma framework through a case study. A case study focused on a set of interviews with practitioners based on a firm located in Germany was used that generates uncaptured insights in previous research of this area. The results of the paper highlight the relevance of building cross-functional teams for achieving continuous improvement and implementing suitable, proven, and appropriated tools. Whereas lean is preferred for scopes as part of processes with few interfaces and medium grade of difficulty, Six Sigma is the most suitable methodology for scopes with a high grade of difficulty or problems involving cross-functional processes. SCOPQ is defined as the costs associated with defects and deficiencies originated by suppliers. For instance, they could include the costs for supplier-related incidents like shortages or failure-related costs, production stop costs, rework costs, complaints, etc. This research not only validates the proposed framework through an in-firm case study, but also confirms the relevance of mitigating and avoiding biases, recommends standardizing processes and texts templates, and the regularly training of the employees involved. Besides of the main goal of investigating Six Sigma's role in reducing quality costs, research results demonstrate the advantage of standardized multilingual texts for the complaint process of global players. The study indentified the influence of English collocations into the complaint process because of the majority of the specialized literature is written in English.